Effects of a Facial Cream Containing the Minor Alkaloid Anatabine on Improving the Appearance of the Skin in Mild to Moderate Rosacea: An Open-Label Case Series Study - Ryan K. Lanier; Amy E. Cohen; Susan H. Weinkle (Karger Publishers, 2013)
Background: Current medical and scientific research indicates that rosacea, a chronic and often debilitating skin condition that primarily affects the central face, may be caused by an overactive or excessive inflammatory immune response. Regardless of etiology, the accompanying redness and inflammation is unsightly and difficult for the patient. Anatabine is an alkaloid from the plant family Solanaceae that has been shown in several preclinical studies to modulate proinflammatory signaling pathways. Objective: A cream containing anatabine was developed and evaluated in an open-label case series study for safety and effects on the appearance of the skin in 10 patients with mild to moderate rosacea. Methods: Patients applied the cream to the face twice daily for a period of 30 days. Patients and the study physician completed safety and efficacy assessments at study end. Results: Results showed that 50% of the patients self-reported improvement in the appearance of their skin, and the physician noted improvement in 70% of the patients. Photographs taken before and after 30 days of cream use provide visual evidence of the improvement in several patients. There were no complications or adverse events reported by any of the patients in the study, indicating that the anatabine cream was safe and very well tolerated. Conclusion: The results of this open-label case series show that a facial cream containing anatabine can improve the appearance of the skin in patients with mild to moderate rosacea and suggest that a double-blind, vehicle-controlled trial in a larger number of subjects is warranted.